Gaya Kepemimpinan Dalam Lembaga Pendidikan Islam - Annisa (Proceedings of Annual Conference on Islamic Educational Management, 2021)
Effective leadership is leadership that can organize work well so that it can be carried out as planned. The better the leadership style and the ability of the leader to organize the work, the better the performance of subordinates. The leadership style will make the task run better and fostering relationships with subordinates will be more effective in achieving daily tasks. Leadership style shows the ability of a leader to be able to optimally increase organizational achievement.